Foreign relations in the ancient Near East : oaths, curses, kingship and prophecy - Freire, Lucas G. (Journal for semitics, 2017)
Oaths and curses, embedded in a covenantal context, were paramount normative mechanisms in the foreign relations between ancient Near Eastern kings. This article provides an account of the political role of covenants and oaths and their religious background, presenting textual evidence denoting the notion that breaking a covenant in foreign relations was a serious offense punishable by divine curses. The article further explores how curses operated, by looking at other texts portraying kings as representatives of their people, and prophets as representatives of the deities, not only to reinforce royal power, but occasionally also to challenge it, particularly in the prediction of divine curses as a reaction to covenant-breaking.